Perbedaan Undang – Undang Ketenagakerjaan Dan RUU Omnibuslaw Cipta Kerja - Sarmadani Sarmadani; Brian Daniel Raja Gukguk; Fahrozi Fahrozi (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
In an effort to support investment growth, the Omnibus Law simplifies the licensing process and provides fiscal incentives. However, criticism emerged mainly from environmental groups who expressed concern over the potential reduction in environmental protection as a consequence of these changes. When the Omnibus Law on Job Creation was passed, mass protests and demonstrations emerged in various cities in Indonesia. Labor unions and activist groups opposed the changes in the law, demanding the maintenance of workers' rights and environmental sustainability. This discontent reflects the divisions among the public regarding the impact of the Omnibus Law on daily life and the future of the country. The government needs to communicate with various stakeholders, including labor unions, employers, and environmental groups, to strike a fair balance and ensure that policies reflect the common interest. The purpose of this paper is to find out the differences between the Manpower Law and the Job Creation Law. The author will use normative legal research conducted by examining secondary data in the form of primary, secondary and tertiary materials. This research is also called library research or document study, because it is mostly done on secondary data in the library. The conclusion of this paper is that the labor cluster of the Job Creation Law (omnibuslaw) is a legal product that relieves employers and is binding on workers. That the comparison of the Manpower Law with the Job Creation Law is a legal product that is made into one big economic and investment issue, in this case the Job Creation Law's labor cluster actually ignores the philosophy of the Manpower Law it replaces.